“You Gave us the Confidence to Talk”. The University Supervisor in a Reflexive Practicum - Saiz Linares, Ángela; Susinos Rada, Teresa (REICE. Ibero-American Journal on Quality, Effectiveness and Change in Education, 2017)
In this paper we present a practicum proposal for initial teacher training articulated as a work of reflection that is developed collaboratively among a group of students and the university tutor. More specifically, this study focuses on the analysis of the functions of the university supervisor as a cornerstone in the development of this program of practicum. We have used a qualitative methodology and we have analyzed information from the teacher diaries, from the group seminars and from the final evaluation interviews. The work has been developed at the University of Cantabria during the academic year 2013-14. The results show the relevance of the university supervisor in terms of moderator of seminars, facilitator of reflection, guide of the reflective processes and as an emotional companion. Some conclusions point to the relational symmetry between tutor and students, the continued support from the supervisor and the consideration of the error as a reason for learning as some factors that have contributed to the development of the climate required for the development of a practicum oriented by reflective and collaborative principles.